2011
DOI: 10.1002/pat.1827
|View full text |Cite
|
Sign up to set email alerts
|

Ordered long‐helical conformation of isotactic polypropylene obtained in constrained environment of nanoclay

Abstract: Special crystallization event of isotactic polypropylene (iPP) in a constrained environment, a layered clay network, was followed by in situ Fourier transform infrared (FTIR) spectroscopy during the cooling process. Before occurrence of nucleation/crystallization, a conformationally ordered phase, which consists of significant amounts of long 31 helices with 14 monomeric units, has been identified for the first time. More importantly, it was found that the long‐ordering helices could play a more important role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Figure shows the FTIR spectra at the wavenumber range of 750–1350 cm −1 for original clays, the neat rubber, and their composites. Four components of Si–O vibration can be roughly divided for different clays: peak I (∼1110 cm −1 ), peak II (∼1035 cm −1 ), peak III (∼1000 cm −1 ), and peak IV (∼984 cm −1 ), which is well agreed with literatures . It has been reported that the position and width of peak II is more sensitive to the interlayer spacing of clays than other peaks in the polymer .…”
Section: Resultssupporting
confidence: 89%
“…Figure shows the FTIR spectra at the wavenumber range of 750–1350 cm −1 for original clays, the neat rubber, and their composites. Four components of Si–O vibration can be roughly divided for different clays: peak I (∼1110 cm −1 ), peak II (∼1035 cm −1 ), peak III (∼1000 cm −1 ), and peak IV (∼984 cm −1 ), which is well agreed with literatures . It has been reported that the position and width of peak II is more sensitive to the interlayer spacing of clays than other peaks in the polymer .…”
Section: Resultssupporting
confidence: 89%
“…This can be an indication of a trimodal semi‐crystalline structure. This structure can be a result of heterogeneous nucleation by the MMT particles . The first maximum is close to the origin and can be attributed to the stacks with a long period of about 4 nm.…”
Section: Resultsmentioning
confidence: 69%
“…One reason for this can be the formation of a constrained region around the MMT particles. In this region, the mobility of polymer chains is restricted . As revealed by our CDF analysis, addition of MMT decreases the size and arrangement of the crystalline lamellae in the PP.…”
Section: Resultsmentioning
confidence: 78%
“…The sizes of AO-80 domains are estimated at the range of 50-400 nm which is close to the SEM observations. Because of the initial sizes of AO-80 powders are above 1 lm, it is believed that the heat mixing is helpful to the nano-dispersivity of AO-80 in the matrix which would affect the properties of the hybrids just as described in nanoclays reinforced polymers [29]. With an increasing amount of AO-80, the tan d peak (tan d max ) of the hybrids gradually shifted to higher temperatures and their peaks also become broader.…”
Section: Morphology Analysismentioning
confidence: 97%
“…It is seen that the modulus of hybrids increases with the increase of filler amounts when they are at the glassy state, whereas the contrary trend is held at their rubbery state. Referring to the rubber hybrids from polymeric fillers, there is the relation among various components [29]:…”
Section: Analyses Of Dynamic Mechanical Property and Their Interactionsmentioning
confidence: 99%